A prospective evaluation of the diagnostic accuracy of the point-of-care VISITECT CD4 advanced disease test in 7 countries - Gils, Tinne; Hella, Jerry; Jacobs, Bart K M; Sossen, Bianca; Mukoka, Madalo; Muyoyeta, Monde; Nakabugo, Elizabeth; Van Nguyen, Hung; Ubolyam, Sasiwimol; Macé, Aurélien; Vermeulen, Marcia; Nyangu, Sarah; et al. (The journal of infectious diseases, 2025)
CD4 measurement is pivotal in the management of advanced human immunodeficiency virus (HIV) disease. VISITECT CD4 Advanced Disease (VISITECT; AccuBio, Ltd) is an instrument-free, point-of-care, semiquantitative test allowing visual identification of CD4 ≤ 200 cells/µL or >200 cells/ µL from finger-prick or venous blood.As part of a diagnostic accuracy study of FUJIFILM SILVAMP TB LAM, people with HIV ≥18 years old were prospectively recruited in 7 countries from outpatient departments if a tuberculosis symptom was present, and from inpatient departments. Participants provided venous blood for CD4 measurement using flow cytometry (reference standard) and finger-prick blood for VISITECT (index text), performed at point-of-care. Sensitivity, specificity, and positive and negative predictive values of VISITECT to determine CD4 ≤ 200 cells/ µL were evaluated.Among 1604 participants, the median flow cytometry CD4 was 367 cells/µL (interquartile range, 128-626 cells/µL) and 521 (32.5%) had CD4 ≤ 200 cells/µL. VISITECT sensitivity was 92.7% (483/521; 95% confidence interval [CI], 90.1%-94.7%) and specificity was 61.4% (665/1083; 95% CI, 58.4%-64.3%). For participants with CD4 0-100, 101-200, 201-300, 301-500, and >500 cells/µL, VISITECT misclassified 4.5% (95% CI, 2.5%-7.2%), 12.5 (95% CI, 8.0%-18.2%), 74.1% (95% CI, 67.0%-80.5%), 48.0% (95% CI, 42.5%-53.6%), and 22.6% (95% CI, 19.3%-26.3%), respectively.VISITECT's sensitivity, but not specificity, met the World Health Organization's minimal sensitivity and specificity threshold of 80% for point-of-care CD4 tests. VISITECT's quality needs to be assessed and its accuracy optimized. VISITECT’s utility as CD4 triage test should be investigated. Clinical Trials Registration: NCT04089423.